(untitled) (Neo Scientific Peer Reviewed Journal, 2023)
This article deals with the popular sayings related to medicine of people famous all over the world, as well as the participation of medical terms in their thoughts and their interpretation in Uzbek when translated from English. The medical expressions presented in this article are characterized by the fact that they are aphorisms expressed not by medical personnel, but by representatives of other fields in general.